Branching out in different directions: Emerging cellular functions for the Arp2/3 complex and WASP-family actin nucleation factors - Kenneth G. Campellone; Nadine M. Lebek; Virginia L. King (European Journal of Cell Biology, 2023)
The actin cytoskeleton impacts practically every function of a eukaryotic cell. Historically, the best-characterized cytoskeletal activities are in cell morphogenesis, motility, and division. The structural and dynamic properties of the actin cytoskeleton are also crucial for establishing, maintaining, and changing the organization of membrane-bound organelles and other intracellular structures. Such activities are important in nearly all animal cells and tissues, although distinct anatomical regions and physiological systems rely on different regulatory factors. Recent work indicates that the Arp2/3 complex, a broadly expressed actin nucleator, drives actin assembly during several intracellular stress response pathways. These newly described Arp2/3-mediated cytoskeletal rearrangements are coordinated by members of the Wiskott-Aldrich Syndrome Protein (WASP) family of actin nucleation-promoting factors. Thus, the Arp2/3 complex and WASP-family proteins are emerging as crucial players in cytoplasmic and nuclear activities including autophagy, apoptosis, chromatin dynamics, and DNA repair. Characterizations of the functions of the actin assembly machinery in such stress response mechanisms are advancing our understanding of both normal and pathogenic processes, and hold great promise for providing insights into organismal development and interventions for disease.